PENDAPATAN USAHATANI POLIKULTUR UDANG WINDU–IKAN BANDENG DAN EFISIENSI PEMASARAN IKAN BANDENG DI KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR - Aldila Putri; Sudarma Widjaya; Eka Kasymir (Lampung University, 2018)
This study aimed to analyze income of tiger shrimp–milkfish and marketing efficiency of milkfish in Pasir Sakti subdistrict of east Lampung Regency. The research location was choosen purposely in Pasir Sakti Subdistrict Lampung Regency. Data of this research was collected during November-January 2016. Respondents of this research were 64 cultivators and 40 traders. This research used survey method, in which samples were chosen by simple random sampling and snowball sampling. The collected data, included primary and secondary data, was analyzed by descriptive qualitative analysis, income analysis, and marketing margins. The results showed that tiger shrimp and milkfish aquaqulture were profitable. There were 2 channels of marketing of milkfish but both of them were inefficient. Marketing margin and profit margin ratio on marketing of milkfish were not prevalent.Key words: Income, marketing efficiency, milkfish